A hotel stay for a respite from work? Examining recovery experience, rumination and well-being among hotel and bed-and-breakfast guests. Issue 4 (11th January 2022) - Chen, Chun-Chu; Han, Jiyoon (Jennifer); Wang, Yao-Chin
Abstract : Purpose: This paper aims to examine the relationship among guests' lodging recovery experience, work-related rumination, guest satisfaction and well-being, within the context of hotels and bed and breakfasts (B&Bs). Design/methodology/approach: The sample included 823 Taiwanese full-time workers. The proposed relationships were tested using partial least square structural equation modeling, and the moderating effects of accommodation types were tested using multi-group analysis. Findings: The research findings indicate that staying at a hotel or B&B provides a respite from work and reduces negative, repetitive thoughts about work issues (work-related rumination). These recovery effects then contribute to customer satisfaction and hedonic and eudaimonic well-being. Practical implications: The findings indicate that practitioners need to develop products that could reduce customers' negative emotional attachments to work and enhance the well-being of customers in a stressful society, which could ultimately contribute to promoting the public health of full-time workers. Originality/value: To the best of the authors' knowledge, this study is the first to examine the stress-recovery aspect of lodging experiences and their impacts on customer satisfaction and well-being. Further insights are demonstrated with the inclusion of work-related rumination.